The Effect of Length of Use of Orthodontic Appliances on the Occurrence of Gingivitis in Adolescents Aged 15-17 Years in Senior High Schools in Jakarta - Ivo Resky Primigo; Chaerita Maulani; Chrisni Oktavia Jusuf (YARSI Dental Scientific Meeting - e Journal, 2024)
Abstract Introduction: Fixed orthodontic appliance is one of the tools used for malocclusion treatment. The parts of the tool stick to the teeth which makes it difficult to clean the teeth, so it will facilitate plaque accumulation and can cause gingivitis. Objective: This study is to determine how the influence of the long use of orthodontic devices on the occurrence of gingivitis in individuals aged 15-17 years and its views in an Islamic perspective. Material and Methods: Type of observational study with cross-sectional study design. The study subjects were individuals aged 15-17 years who wore fixed orthodontic tools taken by purposive sampling method. The study data were taken by questionnaire, measurement of oral hygiene level with dental and oral hygiene questionnaire, and gingival health with Gingival Index (Loe and Silness) and CPITN Index. Results: The prevalence of gingivitis based on the gingival index was obtained as much as 97.2%. The prevalence of subjects who have periodontal disease based on the CPITN index is 88.9%. Discussion: Type of observational study with cross-sectional study design. The study subjects were individuals aged 15-17 years who wore fixed orthodontic tools taken by purposive sampling method. The study data were taken by questionnaire, measurement of oral hygiene level with dental and oral hygiene questionnaire, and gingival health with Gingival Index (Loe and Silness) and CPITN Index. Discussion: There is no significant difference between the duration of use of orthodontic devices and the Gingival Index (p = 0.051). The relationship was not significant between the duration of use of orthodontic devices and the CPITN Index (p = 0.128) and there was also no significant relationship between the duration of use of orthodontic devices and dental and oral hygiene questionnaires (p = 0.853). Conclusion: There is no influence between the duration of use of orthodontic devices and gingivitis.